The Russian Orthodox Church and the Soviet State, 1946–1956: A Decade of the New Orthodoxy - Bennett, Edward M. (A journal of church and state, 1965)
Edward M. Bennett; The Russian Orthodox Church and the Soviet State, 1946–1956: A Decade of the New Orthodoxy, Journal of Church and State, Volume 7, Issue 3, 1